2023
DOI: 10.1002/ece3.10180
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust particles alter gut microbiome and gene expression in the bumblebee Bombus terrestris

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 173 publications
(213 reference statements)
0
3
0
Order By: Relevance
“…Previous work investigating the impact of the heavy metal selenate on B. impatiens (Rothman et al, 2019) and diesel exhaust particles on B. terrestris (Seidenath et al, 2023) also saw alterations in the abundance of core gut symbionts in bees treated with these pollutants. In comparison to control bees, both studies found a lower abundance of Snodgrassella and Lactobacillus bombicola (Lactobacillus Firm-5) in pollution treated bees, Seidenath et al, (2023) also saw changes in Lactobacillus apis (Lactobacillus Firm-5) and Bombiscardova abundance with pollution treatment. Changes in these core microbes were not observed in our data.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work investigating the impact of the heavy metal selenate on B. impatiens (Rothman et al, 2019) and diesel exhaust particles on B. terrestris (Seidenath et al, 2023) also saw alterations in the abundance of core gut symbionts in bees treated with these pollutants. In comparison to control bees, both studies found a lower abundance of Snodgrassella and Lactobacillus bombicola (Lactobacillus Firm-5) in pollution treated bees, Seidenath et al, (2023) also saw changes in Lactobacillus apis (Lactobacillus Firm-5) and Bombiscardova abundance with pollution treatment. Changes in these core microbes were not observed in our data.…”
Section: Discussionmentioning
confidence: 95%
“…However, the core-taxa Snodgrassella and Gilliamella show likewise a better growth rate at elevated temperatures ( Hammer et al., 2021b ), but were decreasing in relative abundance within the course of our sampling period. But even air pollution can selectively erode the microbiota of B. terrestris from important core-taxa like Snodgrassella ( Seidenath et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…10% w/w). More details on the characterization and sampling methods of DEP-samples can be found inHüftlein et al (2023) andSeidenath et al (2023).…”
mentioning
confidence: 99%